2019
DOI: 10.3389/fonc.2019.00962
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Exercise Reduces Kynurenine Pathway Metabolites in Breast Cancer Patients Undergoing Radiotherapy

Abstract: Purpose: Evidence from preclinical studies and trials in healthy volunteers suggests that exercise may modulate the levels of tryptophan (TRP) metabolites along the kynurenine (KYN) pathway. As KYN and downstream KYN metabolites are known to promote cancer progression by inhibiting anti-tumor immune responses and by promoting the motility of cancer cells, we investigated if resistance exercise can also control the levels of KYN pathway metabolites in breast cancer patients undergoing radiotherapy (NCT01468766)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 55 publications
4
37
0
Order By: Relevance
“…To our knowledge, this is the first study that explored the effects of resistance exercise training in the context of kynurenine metabolism pathway in pancreatic cancer patients. The findings are in accordance with our previous study on breast cancer patients showing that chronic resistance exercise counteracts increase in KYN levels and KTR (IDO/TDO) activity during adjuvant radiotherapy [22]. The results reveal that Supervised resistance exercise training can reduce serum KTR (indication of enzyme IDO/TDO) levels compared to Home-based group over time.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…To our knowledge, this is the first study that explored the effects of resistance exercise training in the context of kynurenine metabolism pathway in pancreatic cancer patients. The findings are in accordance with our previous study on breast cancer patients showing that chronic resistance exercise counteracts increase in KYN levels and KTR (IDO/TDO) activity during adjuvant radiotherapy [22]. The results reveal that Supervised resistance exercise training can reduce serum KTR (indication of enzyme IDO/TDO) levels compared to Home-based group over time.…”
Section: Discussionsupporting
confidence: 92%
“…In conclusion, our results suggest that Supervised resistance exercise can downregulate the KTR (IDO/TDO) levels and, hence, may reduce possible disease progression in pancreatic cancer patients undergoing chemotherapy, confirming our earlier findings [22]. Further research in this direction is necessary to clarify the clinical relevance of whether physical exercise can mimic immune therapy and can finally inhibit IDO/TDO.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, as discussed by Fernestrom et al [59], even under conditions of supplementation with extra-Trp, no effect attributable to quinolinic acid toxicity have never been observed in humans. In addition, physical exercise has been shown to prevent per se the eventual brain entry of Trp-derived kynurenine [60] as well as to attenuate the activity of the kynurenine pathway [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Agudelo and colleagues (2014) revealed that the increase in KATs led to a peripheral KYN clearance and thereby mediated resilience to stress-induced depression. However, to the best of our knowledge, only one study in humans showed a counteracting effect of regular exercise on peripheral KYN accumulation investigating resistance exercise in breast cancer patients undergoing radiotherapy (Zimmer et al 2019). Several other studies on regular (mainly aerobic) exercise in different populations did not observe alterations in circulating KYN pathway metabolites (Hennings et al 2013;Kuster et al 2017;Millischer et al 2017).…”
Section: Introductionmentioning
confidence: 71%